A comparative study for gas-phase dehydration of glycerol over H-zeolites - Kim, Yong Tae; Jung, Kwang-Deog; Park, Eun Duck (ELSEVIER, 2011)
The gas-phase dehydration of glycerol was conducted over various H-zeolites, viz. H-ferrierite, H-beta, H-ZSM-5, H-Y and H-mordenite with various SiO2/Al2O3 ratios. For comparison, gamma-Al2O3 and silica-alumina were also examined. Several characterization techniques: X-ray diffraction (XRD), the temperature-programmed desorption of ammonia (NH3-TPD), the temperature-programmed desorption of water (H2O-TPD), temperature-programmed oxidation (TPO) with mass spectroscopy and CHNS analysis were employed to characterize the catalysts. The initial glycerol conversion at 315 degrees C decreased in the following order: silica-alumina > H-beta (25) > H-beta (27) > gamma-Al2O3 > H-mordenite (20) > H-ferrierite (55) > H-ferrierite (20) > H-ZSM-5 (23) similar to H-beta (350) > H-beta (38) similar to H-Y (5.1). H-ferrierite (55) showed the highest selectivity to acrolein at 315 degrees C among the tested catalysts. The glycerol conversion over the solid acid catalysts was strongly dependent on their external surface area. In the case of the H-zeolites, most of the micropores were filled with carbon sources at the initial stage of this reaction. As long as the molar ratio between water and glycerol was in the range from 2 to 11, there was only a small change in the glycerol conversion, while the acrolein selectivity increased noticeably with increasing water content in the feed. The glycerol conversion and acrolein selectivity increased with increasing reaction temperature from 290 degrees C to 340 degrees C over H-ferrierite (55). The glycerol conversion and acrolein selectivity also increased with increasing contact time (W/F-glycerol) which is defined as the ratio between the catalyst's weight (W) and the molar flow rate of glycerol (F-glycerol). (C) 2010 Elsevier B.V. All rights reserved.
Keywords: SUSTAINABLE PRODUCTION; CATALYZED DEHYDRATION; ACROLEIN; ACID; ALUMINA; TEMPERATURE; CONVERSION; CHEMICALS; ALCOHOLS; WATER